Prediction of pulmonary tuberculosis incidence based on epidemiological triad as a preventive measure - Sutriyawan, Agung; Anri, Anri; Imbar, Andri W. J.; Natsir, Ramdhani M.; Pangeran, Paryany; Akbar, Hairil (International Journal of Public Health Science (IJPHS), 2023)
The decline in the incidence of tuberculosis to date still looks very slow, although some efforts have been made to improve case identification and treatment adherence. This study aimed to assess the factors associated with the incidence of pulmonary tuberculosis. The research design for this study was observational analytical with a cross-sectional design. A total of 830 people suspected of tuberculosis, aged over 15 years, and not drug-resistant were selected by simple random sampling. Overall, 59.9% of people are infected with pulmonary tuberculosis. There was a significant association between age (p=0.002) (OR=1.69; 95% CI: 1.22, 2.35), smoking behavior (p=0.000) (OR=2.3; 95% CI: 1.67, 3.30), temperature (p=0.000) (OR=4.2; 95% CI: 2.84, 6.47), humidity (p=0.000) (OR=6.7; 95% CI: 4.69, 9.77), lighting (p=0.000) (OR=4.174; 95% CI: 2.94, 5.92) and incidence of pulmonary tuberculosis. The study showed that tuberculosis was more common among productive age and smokers living in homes with unqualified temperature, humidity, and lighting. Room humidity is the most associated factor with the incidence of pulmonary tuberculosis. Therefore, education on the importance of paying attention to the physical environment of the house to avoid pulmonary tuberculosis is highly recommended.